Proceedings of the 31st Annual International ACM SIGIR Conference on Research and Development in Information Retrieval 2008
DOI: 10.1145/1390334.1390394
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval and feedback models for blog feed search

Abstract: Blog feed search poses different and interesting challenges from traditional ad hoc document retrieval. The units of retrieval, the blogs, are collections of documents, the blog posts. In this work we adapt a state-of-the-art federated search model to the feed retrieval task, showing a significant improvement over algorithms based on the best performing submissions in the TREC 2007 Blog Distillation task [12]. We also show that typical query expansion techniques such as pseudo-relevance feedback using the blog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 8 publications
(9 reference statements)
1
144
0
Order By: Relevance
“…Elsas et al [2] utilize the link structure of Wikipedia for QE in a Blog distillation task and yield significant improvement for retrieval effectiveness, this work also showed that standard PRF does not perform well in a Blog distillation task. Yang et al [3] classify user queries into three types: entity queries, ambiguous queries, and broader queries.…”
Section: Background and Related Workmentioning
confidence: 84%
“…Elsas et al [2] utilize the link structure of Wikipedia for QE in a Blog distillation task and yield significant improvement for retrieval effectiveness, this work also showed that standard PRF does not perform well in a Blog distillation task. Yang et al [3] classify user queries into three types: entity queries, ambiguous queries, and broader queries.…”
Section: Background and Related Workmentioning
confidence: 84%
“…For example, MacKinnon and Vechtomova (2008) expanded queries in the Complex interactive Question Answering (CiQA) track of TREC, by first mapping the terms and phrases in a query to Wikipedia article titles, and then expanding them with anchor texts pointing to these articles. Elsas et al (2008) proposed another method of selecting and weighting anchor texts as QE terms, which showed performance gains in the distillation task of the Blog track. While anchor texts may be useful as QE terms in opinion retrieval, we did not explore their use in this paper, focusing instead on the use of page redirects.…”
Section: Expanding Facets With New Conceptsmentioning
confidence: 99%
“…Within blog (post) search, the TREC Blog track [23,17] plays an important role; having started in 2006, many approaches to blog post finding have been deployed. Among these approaches are the use of credibility indicators [31], recency and link structure [21], and query expansion on external corpora [32,8].…”
Section: Related Workmentioning
confidence: 99%
“…Various ways of improving aspect recall have been introduced: Kurland et al [13] provide an iterative "pseudo-query" generation technique to uncover multiple aspects of a query, using cluster-based language models. Weerkamp and de Rijke [32] explore the use of external corpora to uncover multiple viewpoints on a topic, an approach similar to [8]. Recently, the issue of aspect recall has been addressed using example documents, provided by the user, from which new query terms are sampled [2].…”
Section: Related Workmentioning
confidence: 99%